Styrenated urethane oil synthesis via CuAAC click chemistry approach - ALEMDAR YAYLA, NESLİHAN (ELSEVIER SCIENCE SA, 2015)
In this study, a novel route for the modification of sunflower oil-based partial triglycerides with styrene (St) was described. For this purpose, in the first step, copolymers of St and 4-chloromethyl styrene (P(St-co-CMS)) were synthesized by free radical polymerization (FRP) and controlled/living radical polymerization (nitroxide mediated radical polymerization (NMRP)) methods. In the second step, chloro groups of these samples were transformed into azido groups by using NaN3/DMF and then azido groups were coupled with propargyl alcohol to achieve hydroxyl functional polystyrene chain (PSt-OH) via Cu(I)-catalyzed 1,3-dipolar azide-alkyne cycloaddition (CuAAC) click chemistry approach. Finally, alcohol groups of PSt-OH and the partial glyceride (PG) were combined by the reaction with toluene 2,4-diisocyanate (TDI). As a result, styrenated urethane oil (PG-TDI-PSt) was obtained as an oil-based binder. The structures were determined by FT-IR, H-1 NMR and GPC analyses, and film properties of the products were examined according to the related standards. (PG-TDI-PSt) gave good film properties, and therefore could be considered as an applicable oil-based binder. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Click chemistry; Triglyceride oil; Coating; CuAAC; NMRP; 1,2,3-Triazole group; IN-SITU SYNTHESIS; RADICAL POLYMERIZATION; 1,3-DIPOLAR CYCLOADDITIONS; TERMINAL ALKYNES; GRAFT-COPOLYMERS; POLYMERS; RAFT; AZIDES; COMBINATION; LIGATION